Analisis Keterlambatan Proyek PT. PP Persero Tbk Pada Pembangunan Gedung MRT Dengan Menggunakan Lean Six Sigma Framework - Wijaya, Mochamad Aldi; Widiasanti, Irika (Jurnal Talenta Sipil, 2024)
In general, each construction project has a planned completion time with a set scheduling so that the project can run well. Indonesia is trying to develop infrastructure and public facilities such as the MRT Building Construction Project. This research was conducted at the MRT HUB Building Construction Project Simpang Temu Dukuh Atas Jalan Kendal No. 25, Menteng, Central Jakarta, Special Capital Region of Jakarta 10310 at PT. PP (Persero), Tbk This research aims to obtain factors that cause project delays. This research uses the concept of lean six sigma with the DMAIC phase (Define, Measure, Analyze, Improve, and Control). After being identified, the construction experienced delays in work completion caused by several factors such as overpurchase, delay, and inventories. Lean six sigma helps in finding solutions to minimize delays including not buying goods excessively so as not to cause delays so that workers can work properly without having to wait for the area to be worked on.